Manajemen Pengembangan Potensi Pariwisata Daerah di Desa Wisata Okura Kota Pekanbaru Provinsi Riau - Robby Kurniawan Junaidy; Sri Suwitri; Kismartini Kismartini (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Tourism is one of the development sectors that received government attention to continue to be developed until now, because this sector is considered quite potential for the development of people's economy. The problem is that the number of foreign tourists who enter the city of Pekanbaru tend to decrease in 2011-2016. The lack of tourist attractions in Pekanbaru especially nature tourism, forcing the government of Pekanbaru City to think of new and interesting sights worth developing. The purpose of this study is to identify the potential and condition of tourism, analyzing Planning, Organizing, Actuating and Controlling, and analyzing the supporting and inhibiting factors from the development of regional tourism potential in the Okura Village of Pekanbaru City of Riau Province. The method to be used is qualitative descriptive research. Management of tourism development potential of the region in the Village Tourism Okura Pekanbaru Riau Province has not run optimally. We can see from the lack of supporting infrastructure, resources and finance also become obstacles. And the absence of participation of stakeholders or other tourism developers in Pekanbaru. The recommendation of this research is to provide special fund to focus on development in Okura Tourism Village. Empowering human resources in Okura Tourism Village by providing various coaching and training, upcoming experts to provide special knowledge to the community in Okura Village. Increase cooperation with private parties or parties that would help the development of Okura Tourism Village so that it can create good coordination between the parties.